Impact of a quadrivalent meningococcal ACWY glycoconjugate or a serogroup B meningococcal vaccine on meningococcal carriage: an observer-blind, phase 3 randomised clinical trial - Read, Robert C.; Baxter, David; Chadwick, David R.; Faust, Saul N.; Finn, Adam; Gordon, Stephen B.; Heath, Paul T.; Lewis, David J.M.; Pollard, Andrew J.; Turner, David P.J. (Elsevier, 2014)
Background: Meningococcal conjugate vaccines protect individuals directly, but also confer herd protection by interrupting carriage transmission. This Phase III observer-blind, randomised, controlled study evaluated the effects of meningococcal quadrivalent (ACWY) glycoconjugate (MenACWY-CRM) or serogroup B (4CMenB) vaccination on meningococcal carriage rates in young adults. Methods: University students (aged 18–24 years) from ten sites in England were randomised to receive two vaccinations one month apart: two doses of Japanese Encephalitis vaccine (controls), two doses of 4CMenB (4CMenB), or one dose of MenACWY-CRM then placebo (MenACWY-CRM). Meningococci were isolated from oropharyngeal swabs collected before vaccination and at five scheduled intervals over one year. Primary analysis was cross-sectional carriage one month after the vaccine course; secondary analyses included comparison of carriage at any time point after primary analysis until study termination. Findings: 2954 subjects were randomised (control, n=987; 4CMenB, n=988; MenACWY-CRM, n=979); approximately one-third of each group was positive for meningococcal carriage at study entry. By one month, there was no significant difference in carriage between controls and 4CMenB (Odds Ratios (OR) [95% CI]; 1·2 [0·8−1·7]) or MenACWY-CRM (OR [95% CI], 0·9 [0·6–1·3]) groups. From three months after dose two, 4CMenB vaccination resulted in significantly lower carriage of any meningococcal strain (calculated efficacy 18·2% [95% CI: 3·4–30·8]) and capsular groups BCWY (calculated efficacy 26·6% [95% CI: 10·5–39·9]) compared to control vaccination. Significantly lower carriage rates were also observed in the MenACWY-CRM group compared with controls: calculated efficacies 39·0% [95%CI: 17·3-55·0] and 36.2% [95%CI: 15·6-51·7] for serogroups Y and CWY, respectively. Interpretation: MenACWY-CRM and 4CMenB vaccines reduced meningococcal carriage rates over 12 months post-vaccination and, therefore, may affect transmission where widely implemented.